Autologous adipose‐derived stem cells for the treatment of complex cryptoglandular perianal fistula: A randomized clinical trial with long‐term follow‐up. (30th December 2019) - Garcia‐Arranz, Mariano; Garcia‐Olmo, Damián; Herreros, María Dolores; Gracia‐Solana, José; Guadalajara, Héctor; de la Portilla, Fernando; Baixauli, Jorge; Garcia‐Garcia, Jacinto; Ramirez, José Manuel; Sanchez‐Guijo, Fermín; Prosper, Felipe; ,
Abstract: The aim of this clinical trial (ID Number NCT01803347) was to determine the safety and efficacy of autologous adipose‐derived stem cells (ASCs) for treatment of cryptoglandular fistula. This research was conducted following an analysis of the mistakes of a same previous phase III clinical trial. We designed a multicenter, randomized, single‐blind clinical trial, recruiting 57 patients. Forty‐four patients were categorized as belonging to the intent‐to‐treat group. Of these, 23 patients received 100 million ASCs plus intralesional fibrin glue (group A) and 21 received intralesional fibrin glue (group B), both after a deeper curettage of tracks and closure of internal openings. Fistula healing was defined as complete re‐epithelialization of external openings. Those patients in whom the fistula had not healed after 16 weeks were eligible for retreatment. Patients were evaluated at 1, 4, 16, 36, and 52 weeks and 2 years after treatment. Results were assessed by an evaluator blinded to the type of treatment. After 16 weeks, the healing rate was 30.4% in group A and 42.8% in group B, rising to 55.0% and 63.1%, respectively, at 52 weeks. At the end of the study (2 years after treatment), the healing rate remained at 50.0% in group A and had reduced to 26.3% in group B. The safety of the cellular treatment was confirmed and no impact on fecal continence was detected. The main conclusion was that autologous ASCs for the treatment of cryptoglandular perianal fistula is safe and can favor long‐term and sustained fistula healing. Abstract : Local injection of autologous ASCs plus a "minimally invasive surgery" protocol (no risk of incontinence), in cryptoglandular complex perianal fistula show advantages at long‐term follow‐up (2 years later).